THE ROLE OF INDIVIDUAL STYLE IN SHAPING LITERARY TRADITION - Ochilxonov Abdujalolxon Davron o’g’li, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract The  present  study  examines  the  role  of  individual  style  in  shaping  and transforming  literary  tradition  within  the  framework  of  modern  literary  theory  and stylistics.  Traditionally,  literary  tradition  has  been  perceived  as  a  stable  body  of inherited  forms,  themes,  and  conventions;  however,  contemporary  approaches emphasize  its  dynamic  and  evolving  nature.  Within  this  process,  individual  style emerges as a crucial force that not only reflects personal creativity but also contributes to the renewal and reinterpretation of tradition. The relevance of the research lies in the growing scholarly interest in the interaction between authorial innovation and cultural continuity. The aim of this study is to explore how individual style functions as an agent of change within literary tradition, to analyze the mechanisms through which writers influence and reshape established norms, and to highlight the interdependence of  tradition  and  individuality.  The  research  employs  descriptive,  analytical,  and interpretative methods. The findings demonstrate that literary tradition is not merely preserved  but  actively  constructed  through  the  creative  contributions  of  individual authors.